Adultery As An Absolute Complaint Offense In The New Indonesian Criminal Code: Normative Analysis And Law Enforcement Issues - Raka Indra Pratama (Faculty of Law, Muhammadiyah University of Surabaya, 2025)
The enactment of Law Number 1 of 2023 concerning the Criminal Code (New Criminal Code) brings significant changes in the regulation of criminal acts against morality, particularly adultery, which is closely related to the cultural and moral values ​​of society. This article aims to analyze the regulation of the crime of adultery in the New Criminal Code and identify potential legal issues in its implementation. This study uses a normative legal research method with a statutory and conceptual approach, focusing on Articles 411, 412, and 413 of the New Criminal Code. The results show that the New Criminal Code classifies the crime of adultery into three forms: ordinary adultery, cohabitation or living together as husband and wife outside of marriage, and sexual intercourse with a nuclear family member. Articles 411 and 412 are constructed as absolute complaint offenses that limit the complainant to certain legal subjects, while Article 413 is an ordinary offense. This article also identifies several implementation issues, including the potential criminalization of commercial sex workers (CSWs), legal vulnerabilities for unregistered couples in cohabitation regulations, and the risk of raids or persecution inconsistent with the nature of absolute complaint offenses. Therefore, clarity in implementing regulations and understanding by law enforcement officials are needed to ensure legal certainty.